Corrigendum: miR-31-3p functions as a tumor suppressor by directly targeting GABBR2 in prostate cancer(Front. Oncol., (2022), 12, (945057), 10.3389/fonc.2022.945057) - Choi, Sujin; Lee, Soonchul; Han, Young Hoon; Choi, Junwon; Kim, Isaac; Lee, Jusung; An, Hyun Ju (Frontiers in Oncology, 2024)
In the published article, there was a mistake in Figure 4 as published. The image of LNCap co-transfected with empty vector and control miRNA in Panel C was mistakenly mixed up with the image of the LNCap co-transfected with GABBR2 vector and miR-31-3p in Panel D. The corrected Figure 4 appears below. miR-31-3p-induced tumor suppressive functions are associated with downregulation of GABBR2. (A) Restoration of GABBR2, p-ERK and p-JNK protein levels after ectopic expression of Myc-DDK-tagged-GABBR2. DU145, PC-3 and LNCap cells were transfected with a mixture of miR-31-3p (20 nM) and GABBR2 expression vector (4 μg). An unpaired two-tailed Student’s t-test was used to calculate P values. Error bars represent mean ± SEM. *P value < 0.05, **P value < 0.01 and ***P value < 0.001 vs. Cont (n = 3). (B) Ectopic expression of GABBR2 suppresses miR-31-3p-induced apoptosis of DU145, PC-3, and LNCap cells. An unpaired two-tailed Student’s t-test was used to calculate P values. Error bars represent mean ± SEM. ***P value < 0.001 vs. Cont (n = 3). (C, D) Ectopic expression of GABBR2 restores miR-31-3p-mediated inhibition of PC cell migration and invasion. An unpaired two-tailed Student’s t-test was used to calculate P values. Error bars represent mean ± SEM. *P value < 0.05, **P value < 0.01 and ***P value < 0.001 vs. Cont (n = 3). The authors apologize for this error and state that this does not change the scientific conclusions of the article in any way. The original article has been updated.
Keywords: GABBR2; miR-31-3p; miRNA; prostate cancer; tumor suppressor gene